Matrices, moments, and quadrature with applications - Golub, Gene H. (Gene Howard), 1932-2007 (Princeton series in applied mathematics., 2010)
This computationally oriented work describes and explains the mathematical relationships among matrices, moments, orthogonal polynomials, quadrature rules, and the Lanczos and conjugate gradient algorithms.